Tanggungjawab Sosial Bank Syariah di Indonesia: Analisis Maqashid Syariah - Ekarina Katmas; Evie Syalviana (At-Thariqah: Jurnal Ekonomi, 2021)
Islamic banking are banking that are based on islamic law, both from the work system and the activities in it all in accordance with islamic law. Islamic bank ethics and social responsibility must also be in accordance with islamic principles. This research was conducted to determine and analysis ethical disclosure and social responsibility based on the maqashid sharia perspective on islamic banks in Indonesia. The objects used in this study are 11 Banks taken from Sharia Commercial Banks and Banks that have Sharia Business Units registered at Bank Indonesia. The study uses annual report in 2017 on the official website. Analysis of data using qualitative descriptive analysis. The result of this study obtained ethical disclosure based on islamic banking ethics disclosure index of 69%, the highest total disclosure were vision and mission indicators with a score of 86%, and the lowest value obtained by the zakat indicator with a value 0f 45%. While the disclosure of social responsibility in the perspective of maqashid sharia based on islamic social reporting index was 66% overall. For product and service indicators is an indicator that has the highest disclosure value of 100%, the lowest value is obtained by environmental indicators with a value of only 15%. From this it can be concluded that the communication between the banks management and stakeholders is necessary, in order to create sharia purpose is to benefit the ummah.